THE PRACTICE OF CRITICAL THINKING SKILLS IN TEACHING MATHEMATICS: TEACHERS’ PERCEPTION AND READINESS (Malaysian Journal of Learning and Instruction, 2022)
Purpose - This study was conducted to identify the relationship and influence of mathematics teachers’ perception and readiness on the practice of critical thinking skills (CTS) in implementing pedagogical processes in secondary schools.Methodology - Participants of the study consisted of 226 mathematics teachers who taught in three different secondary school categories, namely high performing schools (HPS), moderate performing schools (MPS) and low performing schools (LPS) throughout the state of Kelantan, Malaysia. The instrument used was adapted from Thurman (2009) to test the teachers’ perception of CTS, while the teachers’ readiness to apply CTS was adapted from Nagappan (2001) and Yusof and Ibrahim (2012). Besides, measurement of the teachers’ practice of CTS was adapted from Aldegether (2009), Barak and Shakhman (2008), and Shim and Walczak (2012).Findings - Teachers’ perception, readiness, and CTS practice in mathematics teaching were high in HPS but low in LPS. There was a strong positive relationship between teachers’ perception of CTS practice and teachers’ readiness to implement CTS practice in mathematics teaching. In addition, a total of 65 percent variance was contributed by both variables, namely teachers’ perception and teachers’ readiness for CTS practice in mathematics teaching, and this contribution was very high.Significance - The findings of the study also proved that the practice of CTS has improved the pedagogical quality of teachers, especially in meeting the needs of 21st century learning in the classroom. The emphasis on higher order thinking skills (HOTS) is a continuation of the excellence of teaching strategies through a variety of planned learning resources.